A large animal model for standardized testing of bone regeneration strategies - James C. Ferguson; Stefan Tangl; Dirk Barnewitz; Antje Genzel; Patrick Heimel; Veronika Hruschka; Heinz Redl; Thomas Nau (BMC Veterinary Research, 2018)
Abstract Background The need for bone graft substitutes including those being developed to be applied together with new strategies of bone regeneration such as tissue engineering and cell-based approaches is growing. No large animal model of bone regeneration has been accepted as a standard testing model. Standardization may be the key to moving systematically towards better bone regeneration. This study aimed to establish a model of bone regeneration in the sheep that lends itself to strict standardization and in which a number of substances can be tested within the same animal. To this end the caudal border of the ovine scapula was used as a consistent bed of mineralized tissue that provided sufficient room for a serial alignment of multiple experimental drill holes. Results The findings show that for the sake of standardization, surgery should be restricted to the middle part of the caudal margin, an area at least 80 mm proximal from the Glenoid cavity, but not more than 140 mm away from it, in the adult female Land Merino sheep. A distance of 5 mm from the caudal margin should also be observed. Conclusions This standardized model with defined uniform defects and defect sites results in predictable and reproducible bone regeneration processes. Defects are placed unilaterally in only one limb of the animal, avoiding morbidity in multiple limbs. The fact that five defects per animal can be evaluated is conducive to intra-animal comparisons and reduces the number of animals that have to be subject to experimentation.